2017
DOI: 10.1002/hipo.22804
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of perineuronal nets increases the frequency of sharp wave ripple events

Abstract: Hippocampal sharp wave ripples (SWRs) represent irregularly occurring synchronous neuronal population events that are observed during phases of rest and slow wave sleep. SWR activity that follows learning involves sequential replay of training-associated neuronal assemblies and is critical for systems level memory consolidation. SWRs are initiated by CA2 or CA3 pyramidal cells (PCs) and require initial excitation of CA1 PCs as well as participation of parvalbumin (PV) expressing fast spiking (FS) inhibitory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 84 publications
3
32
0
Order By: Relevance
“…Since each PV interneuron can contact hundreds of pyramidal cells (Andersen et al, 2006), PNN disruption may influence pyramidal cell activity at the population level. Consistent with this, recent findings in rodents show that PNN diminution has the potential to enhance both the power of gamma oscillations and the frequency of sharp wave ripple events (Lensjo et al, 2017b; Sun et al, 2018). Similarly, chronic venlafaxine treatment stimulates PNN diminution and an MMP-9-dependent increase in carbachol-induced gamma oscillatory power in ex vivo hippocampal slices (Alaiyed et al, 2019).…”
Section: Increased Matrix Metalloprotease Activity Might Ameliorate Dsupporting
confidence: 71%
“…Since each PV interneuron can contact hundreds of pyramidal cells (Andersen et al, 2006), PNN disruption may influence pyramidal cell activity at the population level. Consistent with this, recent findings in rodents show that PNN diminution has the potential to enhance both the power of gamma oscillations and the frequency of sharp wave ripple events (Lensjo et al, 2017b; Sun et al, 2018). Similarly, chronic venlafaxine treatment stimulates PNN diminution and an MMP-9-dependent increase in carbachol-induced gamma oscillatory power in ex vivo hippocampal slices (Alaiyed et al, 2019).…”
Section: Increased Matrix Metalloprotease Activity Might Ameliorate Dsupporting
confidence: 71%
“…In terms of flexibility, PNN abundance is modulated by proteolytic processing. While experimental studies often utilize hyaluronidase or chondroitinase to affect PNN degradation [ 24 , 47 , 48 ], MMPs and ADAMTS proteins likely represent important physiological modulators of the PNN [ 1 ]. This is supported by recent work showing that PNN is more abundantly expressed in juvenile MMP-9-null mice [ 49 ].…”
Section: Regulation Of Pnnmentioning
confidence: 99%
“…Though PNN staining in the hippocampus is less robust than that in the visual cortex [ 17 ], reduced PV activity could nonetheless influence population activity in this brain region as well. In recent work, we have observed that ex vivo treatment of hippocampal slices with hyaluronidase or chondroitinase can increase the frequency of sharp-wave ripple (SWR) events [ 48 ]. The sharp wave reflects depolarization of CA1 pyramidal cells by synchronous discharge of CA3 axonal inputs [ 148 ].…”
Section: Implications Of Altered Pnn Integrity At the Network Levementioning
confidence: 99%
“…Although the role of PNNs surrounding PC pyramidal cells is undetermined, PNNs have been shown to restrict synaptic plasticity in the hippocampal CA2 pyramidal cells (Carstens et al, 2016). Loss of PNNs may also render interneurons more susceptible to oxidative stress due to astrocytic activation as early as 8 days after surgery, potentially leading to a reduction of PV mRNA expression and a potential disruption of oscillatory activity as previously shown in the hippocampus (Yamada et al, 2015; Sun et al, 2018). The number of GAD-immunopositive neurones in the PC of the pre-motor model was similar to that in the sham animals, suggesting a downregulation of CBPs rather than neuronal death.…”
Section: Discussionmentioning
confidence: 81%